Enhancing integrated development planning to alleviate the legacy of apartheid planning - Mokgalong, Samuel (School of Architecture, Planning and Geomatics, 2017)
The research serves to gain a deeper understanding as to the reasons behind the persistence of the apartheid planning legacy. This is done through a discourse analysis of integrated development planning, a planning tool introduced into South Africa to address the consequences of apartheid. Thus the aim of the Research is to: 1. Understand the underlying values and meanings of the discourses used in the many iterations of the City's Integrated Development Plans (IDPs); 2. Explore if, and how, these values and meanings have changed since 2002; 3. Establish what has prompted a change in the adopted values and meanings contained within the different iterations of the City's IDPs; and 4. Critically assess how altered values and meanings have impacted on planning actions and outcomes. Research Methods used are the case study method, discourse analysis, institutional ethnography and archival research. More specifically, a case study on Cape Town and a discourse analysis of different iterations of the City's IDP (a method done in conjunction with archival research). These IDPs being the 2002, 2007 and 2012 IDP. The findings show that the values and meanings have indeed changed since the 2002 IDP. This change is mainly attributed to the dynamic nature of Cape Town's political context over time, as well as its socio-economic context. This change has resulted in the poor no longer being prioritized and empowered through integrated development planning. It is also seen that the shift towards a more managerial approach to planning, which is seen in the IDP, has come at the expense of actions and outcomes which successfully redress the legacy of apartheid planning. A result which clearly contributes to the persistence of the apartheid planning legacy.